2013
DOI: 10.1111/evj.12130
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in in vitro antimicrobial susceptibility patterns of bacteria isolated from foals with sepsis: 1979–2010

Abstract: SummaryReasons for performing the study: Monitoring the development of antimicrobial resistance is important for the rational selection of appropriate antimicrobial drugs to initiate treatment of foals with sepsis. Objectives: To identify temporal trends in antimicrobial susceptibility patterns of bacteria isolated from foals with sepsis. Study design: Retrospective review of medical records. Methods: Foals aged <30 days with a diagnosis of sepsis, confirmed by culture of bacteria, were included. Susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 23 publications
(56 reference statements)
4
82
0
Order By: Relevance
“…Few studies have reported isolation of ESBL-producing Enterobacteriaceae from equine infections such as infected wounds, septic arthritis and sepsis (Dolejska et al, 2011;Dierikx et al, 2012;Smet et al, 2012;Walther et al, 2014). Resistance rates against 3rd or 4th generation cephalosporins in Enterobacteriaceae from clinical samples are 5-14% and an increase over time was noted (Clark et al, 2008;Dierikx et al, 2012;Theelen et al, 2014). In our collection, the prevalence of pESBL-producing E. coli and K. pneumoniae ssp.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Few studies have reported isolation of ESBL-producing Enterobacteriaceae from equine infections such as infected wounds, septic arthritis and sepsis (Dolejska et al, 2011;Dierikx et al, 2012;Smet et al, 2012;Walther et al, 2014). Resistance rates against 3rd or 4th generation cephalosporins in Enterobacteriaceae from clinical samples are 5-14% and an increase over time was noted (Clark et al, 2008;Dierikx et al, 2012;Theelen et al, 2014). In our collection, the prevalence of pESBL-producing E. coli and K. pneumoniae ssp.…”
Section: Discussionmentioning
confidence: 67%
“…showed high resistance rates against b-lactam antimicrobials. Resistance towards penicillin is frequent in equine isolates (Clark et al, 2008;Theelen et al, 2014), while resistance towards other b-lactams, especially cephalosporins, is rarely reported (Clark et al, 2008;Theelen et al, 2014). Here, 68% of staphylococci showed cephalosporin resistance due to methicillin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations